Improving Creative Writing for Young Learners using CTL Post COVID 19 - Wahyuni, Elli Setiyo (Lingual Journal of Language and Culture, 2021)
The research aims to implement contextual teaching and learning approach in writing skill which is integrated in the lesson plan. The methodology conducted in the study is a case study taken in one of elementary school in Indonesia. The purpose is to investigate the improvement of students’ writing skill post covid 19.  There are five strategies of contextual teaching and learning approach, namely relating, experiencing, applying, cooperating, and transferring (REACT). The implementation is providing practices on descriptive and narrative writing. The assessment is the learning project related to real-world context and writing story telling. The results of the research are expected to give impact for enhancing the students’ creative writing, to provide learning process which is practical in real world situation, and to assign a lesson plan which is relevant with the current development in English language teaching. Keywords: contextual teaching and learning, creative writing, lesson plan, REACT